2010
DOI: 10.1159/000315096
|View full text |Cite
|
Sign up to set email alerts
|

CHOP-dependent Regulation of p21/waf1 During ER Stress

Abstract: The transcription factor CHOP/GADD153 is induced during the unfolded protein response (UPR) and is associated to the induction of ER stress-related apoptosis. However, how the transition between the pro-survival and the pro-apoptotic role of ER stress is being orchestrated remains poorly understood. Here we show that tunicamycin, an antibiotic promoting ER stress, suppresses the expression of p21, a tumor suppressor that induces cell cycle arrest and inhibits apoptosis. This suppression of p21 levels was indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
46
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 20 publications
(28 reference statements)
10
46
0
2
Order By: Relevance
“…2B, lane 8). CHOP induces apoptosis in part by downregulating p21 (36). Consistent with this finding, we also observed a decrease of p21 protein level in cells that were depleted of p97 or overexpressed the ATPase-inactive mutant (Fig.…”
Section: Resultssupporting
confidence: 89%
“…2B, lane 8). CHOP induces apoptosis in part by downregulating p21 (36). Consistent with this finding, we also observed a decrease of p21 protein level in cells that were depleted of p97 or overexpressed the ATPase-inactive mutant (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Is it a novel independent pro-apoptotic pathway, or a previously uncharacterised pleotropic downstream effect of the ATF4-CHOP axis? As it was suggested previously by the same group, the second hypothesis sounds more plausible as p21 expression seems to be governed by CHOP (Mihailidou et al 2010). This was demonstrated by the absence of p21 downregulation in the tunicamycin-induced CHOP KO mice and also by the drop in p21 mRNA and protein levels in the CHOP-transfected lung cancer cells.…”
mentioning
confidence: 60%
“…Consistent with this notion, during its earlier stages the UPR is pro-survival while at subsequent stages it becomes pro-apoptotic (Ron & Walter 2011). Results of previous studies at our laboratory indicated that an inverse correlation between the activation of the UPR and the expression of P21 exists (Mihailidou et al 2010). P21 is a cell-cycle regulator with strong anti-apoptotic activity produced by both cellautonomous and non-cell-autonomous mechanisms (Blagosklonny 2002, Roninson 2002, Weiss 2003, Trimis et al 2008.…”
Section: Introductionmentioning
confidence: 94%